New insights into the infection of the American cockroach Periplaneta americana nymphs with Metarhizium anisopliae s.l. (Ascomycota: Hypocreales) - Gutierrez, Alejandra Concepción (2016)
Aims: To study the marked resistance of Periplaneta americana to entomopathogenic Metarhizium anisopliae. Methods and Results: The low susceptibility of 4th instar nymphs applied topically with conidia seemed to be related to an active removal of conidia by the cockroach and to a disabled or retarded germination and subsequent development of conidia on the cuticle (up to 80% germination in the next 7 days after application). Inhibitions or delays of germination were related to the composition of the epicuticular fatty acids (30·1% w/w oleic, 28·3% w/w linoleic, 24·5% w/w palmitic and 11·7% w/w stearic acid) reported here. Propagules invading the nymphs through the cuticle took at least 3 days to reach the haemocoel, and no propagules were found after day 8 post-treatment. Strain IP 46 infected >50% of nymphs treated with doses ≥2 × 104 hyphal bodies (HB) nymph−1 and reduced the survival of nymphs ≤50%. Most nymphs (>70%) survived after injection of 6 × 103 and 2 × 103 HB nymph−1. Conclusions: Findings emphasize a distinct resistance of nymphs of the American cockroach to infections by M. anisopliae. Significance and Impact of the Study: Our findings provide support for the development of biological control of this synanthropic cockroach pest.